Tricking search engines - Marcos, Mari-Carmen (Anuario ThinkEPI, 2008)
Knowing the factors that search engines consider in their ranking results is key for webmasters. This knowledge is an advantage for a website´s owner, as the site improves its position in ranking results, and for the search engines because they have access to more information about the site´s content to determinate the ranking. Websites that use search engine optimization techniques avoid the use of images without alternative text and try to link and be linked by related content sites. Good use of these search engine optimization (SEO) techniques is called "white hat SEO"; its main feature is that websites are designed with users in mind and without forgetting how search engines work. Nevertheless, web design oriented toward search engines rather than users is possible; it means websites are designed for ranking results, abusing SEO techniques to deceive search engines, such as with hidden text or small fonts, two of the most common strategies. When search engines discover these unethical techniques, called "black hat SEO", websites are punished with poor rankings.